PREPARATION MASTERS OF SOCIAL WORK FOR MEANINGFUL OF METHODOLOGY OF SOCIO-ASSISTEND ACTIVITIES - Nadezhda Klushina (Вестник Северо-Кавказского федерального университета)
The article analyzes the importance of the methodological training of masters of social work. The article reveals the author's understanding ofthe socio-assisted activities. The author justifies the maintenance ofdiscipline «Methodology of socio-assisted activity» in the context of understanding the essence of the future profession. The article suggests various forms ofpractical training for the development ofmethodological approaches. The author analyzes the impact of the discipline on the awareness of the value of masters future careers.